Enhanced tolerance of transgenic rice overexpressing Arabidopsis thaliana Nucleoside Diphosphate Kinase (AtNDPK2) against various environmental stresses - Manigbas, Nonvie L.; Park, Dong-Soo; Park, Soo-Kwon; Han, Sang-Ik; Park, Hyang-Mi; Woon-Ha, Hwang; Sang-Min, Kim.; Hoe-Jeong, Wang.; Hang-Won, Kang.; Kim, Doh-Hoon; Yun, Dae-Jin; Yi, Gihwan (2011)
Multiple tests to assess different abiotic stresses in rice overexpressing the Arabidopsis thaliana Nucleoside Diphosphate Kinase (AtNDPK2) gene have not been extensively studied. We present the responses of transgenic AtNDPK2 rice lines driven by two different promoters from sweet potato (SWPA2) and cauliflower mosaic virus (CaMV 35S). Transgenic rice lines were evaluated in terms of their tolerance for various abiotic stresses, including cold, drought, ozone, salinity and ultraviolet irradiation. Our results indicate that the transgenic lines were highly tolerant of osmotic stress at 20% polyethylene glycol (PEG) and of salt stress at 100 mM NaCl. The same tolerance was observed with the 5-h continuous UV treatment and ozone. Moderate to weak tolerance for cold and salinity was observed. Our results suggest that the AtNDPK2 gene was responsible for the tolerance for various abiotic stresses in rice.
Keywords: Rice -- Genetics; Climate change